Belis and Women’s Dignity: Cultural and Catholic Reflections in Wolosambi - Policarpus; Antonius Denny Firmanto (Asosiasi Ahli Filsafat Keilahian Indonesia, 2025)
The belis tradition in Wolosambi society is a cultural institution affirming solidarity, reciprocity, and women’s dignity. Historically, it strengthened family bonds and honored women as the center of social life. Yet, contemporary pressures have shifted its meaning toward materialism, creating risks of commodification and reinforcing patriarchy. This study applies a qualitative-descriptive approach with cultural hermeneutics to explore the symbolic values of belis, its effects on women’s dignity, and its theological significance. The study was conducted in Wolosambi, Flores, Indonesia. Findings highlight its dual character: while affirming women’s vital role, it may also reduce them to economic objects. Through Catholic theological reflection, especially Mulieris Dignitatem and inculturation principles, this article proposes a reinterpretation of belis that preserves cultural identity while promoting justice, gender equality, and human dignity. The study contributes theoretically to contextual theology by articulating belis as a culturally embedded locus of moral meaning, and practically by offering pastoral and inculturation-oriented guidelines for safeguarding women’s dignity within local marriage practices.